Effect of non-abrupt doping and interfacial profiles on the carrier sheet density in one-side modulation-doped GaN/AlGaN quantum wells - Enders Neto, Bernhard Georg (2009)
The results of an accurate theoretical study on the effects of non-abrupt doping and interfacial profiles on the electron sheet density in one-side modulation-doped wurtzite GaN/AlGaN single quantum wells at low temperatures are presented. We solve coupled Schr¨odinger and Poisson equations self-consistently via the finite difference method. By employing a proper discretization on a nonuniform grid and taking into account the strong piezoelectric and spontaneous polarization fields exhibited by the wurtzite III-nitride heterostructures, a substantial increase in the 2DEG density is predicted with the increase of the donor diffusion length and the reduction of the spacer thickness.